Coronary Heart Disease risk profile among women attending Tertiary Care Hospital in Southern Karnataka, India - Hoogar, varsha; M., Renuka; Kulkarni, Prashanth; Desai, Nagaraja (International Journal Of Community Medicine And Public Health, 2017)
Background: Present study was conducted to assess the risk factors of CHD in women who had undergone Coronary Angiography for CHD evaluation. Objectives of the study were to assess the CHD Risk profile among women attending Tertiary Care Hospital at Mysore city and to enlist the clinical presentation of women admitted to tertiary care Hospital. Settings and Design: Hospital based cross sectional study. Methods: All the women who were admitted to the Department of Cardiology from April 2015 to January 2016 were interviewed using pre structured proforma. Details of the female patients who had undergone Angiography from September 2013 to March 2015 were also collected from Medical Record Section of the Hospital. Statistical Analysis: Proportion and mean were used for relevant univariate analysis and significance of association was tested using appropriate tests of significance. Results: 17% of women were known cases of CHD. 87.4% of women were admitted with the symptom of chest pain. 44% of women who presented with IHD belonged to normal and underweight BMI category. Among the clinically suspected or diagnosed to be cases of CHD, 75% had blocks in their coronaries. Single artery block (29.7%) and triple artery block (22.5%) were predominant. Left anterior descending artery had significant block (>70%) in 36% of women. Left circumflex artery and right coronary arteries showed significant blocks in 26% and 22.5% participants. Conclusions: Earlier age of presentation, higher proportion of coronary blocks in majority of study women belonging to normal or underweight BMI category are alarms of changing pattern of CHD in Indian women.